Somatic symptoms, perceived stress, and preventive behavior during the COVID-19 pandemic - A. A. Zolotareva (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Numerous studies of the COVID-19 effects on mental health have documented increases in anxiety and depressive symptoms, panic and adjustment disorders, suicidal ideation and suicide attempts, somatic and psychological distress, feelings of loneliness, and alcohol use problems [21]. These findings suggest the need for further examination of the COVID-19 effects on mental health and adherence to preventive behavior regarding the risks of SARS-CoV-2 infection.Objective. The aim of this study was to examine the prevalence and relationship between somatic symptoms, perceived stress, and preventive behavior during the COVID-19 pandemic in Russia.Material and Methods. The participants were 1,987 volunteers who were recruited with the help of Anketolog, an empirical data collection company in Russia. All respondents completed a questionnaire with a sociodemographic form and Russian versions of the Somatic Symptom Scale-8, Perceived Stress Scale-10, and COVID-19 Preventive Behavior Index.Results. Results showed that 39.1% of Russians had clinically significant somatic symptoms, 81% of Russians experienced moderate to high perceived stress, and from 46.5% to 84.4% of Russians were willing to follow some form of COVID-19 pandemic preventive behavior. Russians with somatic symptoms experienced more perceived stress than Russians without somatic symptoms, while Russians with higher perceived stress did not differ from Russians with lower perceived stress in frequency and severity of somatic symptoms.Conclusion. Preventive and psychoeducational interventions can be useful in reducing somatization and perceived stress, maintaining and increasing the adherence of Russians to preventive behavior during the COVID-19 pandemic.